Philo of Alexandria, On planting : introduction, translation, and commentary - Philo, of Alexandria, (Philo of Alexandria Commentary Series;, 2020)
"The Jewish exegete and philosopher Philo of Alexandria has long been famous for his complex and spiritually rich allegorical treatises on the Greek Bible. The present volume presents first translation and commentary in English on his treatise De plantatione (On planting), following on the volume devoted to On cultivation published previously by the same two authors. Philo gives a virtuoso performance as allegorist, interpreting Noah's planting of a vineyard in Genesis 9.20 first in theological and cosmological terms, then moving to the spiritual quest of both of advanced souls and those beginning their journey. The translation renders Philo's baroque Greek into readable modern English. The commentary pays particular attention to the treatise's structure, its biblical basis and its exegetical and philosophical contents".